Peripapillary atrophy area predicts the decrease of macular choroidal thickness in young adults during myopia progression - Xun Xu; Jianfeng Zhu; Ying Fan; Luyao Ye; Ya Shi; Menghan Li; Qiuying Chen; Guangyi Hu; Jiamin Xie; Jiangnan He (BMJ Open Ophthalmology)
Objective This study aimed to investigate the influence of peripapillary atrophy (PPA) area and axial elongation on the longitudinal changes in macular choroidal thickness (ChT) in young individuals with myopia.Methods and analysis In this longitudinal investigation, 431 eyes—342 categorised as non-high myopia (non-HM) and 89 as HM—were examined for 2 years. Participants were examined with swept-source optical coherence tomography. The macular ChT, PPA area and axial length (AL) were measured at baseline and follow-up visits. Multiple regression analysis was performed to identify factors associated with ChT changes. The areas under the receiver operating characteristic curves were analysed to ascertain the predictive capacity of the PPA area and axial elongation for the reduction in macular ChT.Results Initial measurements revealed that the average macular ChT was 240.35±56.15 µm in the non-HM group and 198.43±50.27 µm in the HM group (p<0.001). It was observed that the HM group experienced a significantly greater reduction in average macular ChT (−7.35±11.70 µm) than the non-HM group (−1.85±16.95 µm, p=0.004). Multivariate regression analysis showed that a greater reduction of ChT was associated with baseline PPA area (β=−26.646, p<0.001) and the change in AL (β=−35.230, p<0.001). The combination of the baseline PPA area with the change in AL was found to be effective in predicting the decrease in macular ChT, with an area under the curve of 0.741 (95% CI 0.694 to 0.787).Conclusion Over 2 years, eyes with HM exhibit a more significant decrease in ChT than those without HM. Combining the baseline PPA area with the change in AL could be used to predict the decrease of macular ChT.